Survey of Primary Care and Mental Health Prescribers' Perspectives on Reducing Opioid and Benzodiazepine Co-Prescribing Among Veterans. Issue 3 (22nd August 2016) - Hawkins, Eric J.; Malte, Carol A.; Hagedorn, Hildi J.; Berger, Douglas; Frank, Anissa; Lott, Aline; Achtmeyer, Carol E.; Mariano, Anthony J.; Saxon, Andrew J.
Abstract: Background. Due to the involvement of opioids and benzodiazepines in rising pharmaceutical overdoses, a reduction in coprescribing of these medications is a national priority, particularly among patients with substance use disorders and other high-risk conditions. However, little is known about primary care (PC) and mental health (MH) prescribers' perspectives on these medications and efforts being implemented to reduce coprescribing. Design. An anonymous survey. Setting. One multisite VA health care system. Subjects. Participants were 55 PC and 31 MH prescribers. Methods. Survey development was guided by the Promoting Action on Research Implementation in Health Services (PARIHS) conceptual framework. PC and MH prescribers of opioids or benzodiazepines were invited to complete an anonymous electronic survey. Responses were collapsed to highlight agreement, disagreement, and neutrality and summarized with means and percentages. Results. Over 80% of both prescriber groups reported concern about concurrent use and > 75% strongly agreed with clinical practice guidelines (CPG) that recommend caution in coprescribing among patients with high-risk conditions. More than 40% of both prescriber groups indicated that coprescribing continues because of beliefs that patients appear stable without adverse events and tapering/discontinuation is too difficult. Over 70% of prescribers rated strategies for addressing patients who refuse to discontinue, more time with patients, and identification of high-risk patients as helpful in reducing coprescribing. Conclusion. Despite strong agreement with CPGs, prescribers reported several barriers that contribute to coprescribing of opioids and benzodiazepines and challenge their ability to taper these medications. Multiple interventions are likely needed to reduce opioid and benzodiazepine coprescribing.